Strategi NGO Lingkungan Greenpeace Indonesia Dalam Mendorong Transisi Energi Baru dan Terbaharukan (EBT) di Tengah Kontroversi Realisasi Net Zero Emission (NZE) 2060 di DKI Jakarta - Nugroho, Bati; Angela, Deni (Jayapangus Press, 2024)
Net Zero Emission (NZE) 2060 is a global program that start being realized by 197 countries including Indonesia, which is recommended to be implemented through the New and Renewable Energy (EBT) transition. Unfortunately, the process of realizing NZE 2060 being undertaken by the government for the DKI Jakarta area is currently being called by the Environmental Non-Government Organization (NGO) Greenpeace Indonesia as controversial because it places too much emphasis on electric vehicles compared to EBT. This research aims to analyze the strategy implemented by Greenpeace Indonesia in pushing EBT transition to accelerate the realization of NZE 2060 in DKI Jakarta. The research method used is a qualitative approach with a descriptive research type whose data was obtained through interviews and literature study. Results and research analysis show that since 2008 Greenpeace Indonesia's strategy has succeeded in having an influence in minimizing controversy and encouraging the use of EBT in DKI Jakarta. Before holding campaign activities or demonstrations, Greenpeace Indonesia always collects data through research as initial capital to determine the narrative that will be presented and subsequent actions. Greenpeace Indonesia also completes its strategy by introducing EBT directly to civil society communities to be a role model and increase community participation in the realization of NZE program. In conclusion, collaboration and synergy are needed between the government and environmental NGOs as a forum for civil society to smoothen the EBT transition and accelerate the realization of NZE 2060 program.